Designing an Augmented Reality Strategy: ELearning/ Extensive Reading - Tunik Muharlisiani, Lusy; Kurniasih, Nuning; Istiqomah, Lilik; Safriyani, Rizka; Abid, Nuskhan; Rizki Ramadhani, Yulia; James Hukom, Salmon; Lolo Siahaan, Basar; Anas Ahmadi, Edy; Hendrawati, Erna (International Journal of Engineering and Technology, 2018)
This paper aims to see the students’ responses toward the use of Augmented Reality in English learning as the application has been used in some courses in some levels of students in UWKS.Â The study implemented the quasi-experimental methodology by applying for the program to two groups, controlled and experimental.Â Â Â Â Â Â Â Survey method along with the use of questionnaire was used for data collection.Â The finding and discussion showed that Augmented Reality was well -utilized in the activity of English language teaching. However, the utilization needed to be more optimized and explored due to most of them were first time users. Â